A miniature stub-loaded antenna optimized at VHF band for FSR sensor application / Hasrul Hisyam Harun - Harun, Hasrul Hisyam (2014)
The concept of forward scattering radar briefly introduce in this paper which is the suggested application for monopole antenna design proposed. The concept of antenna monopole design, miniature technique and optimization method proposed with problem statement, objectives and research methodology are explained in earlier chapter of this article. This supported with a reviewed of previous experimental result from several researches as references. This article demonstrated a miniature monopole antenna optimization at VHF band (30-300MHz) for FSR sensor application. Stub-loaded technique is applied in this design by placing the stub at strategic position along the antenna. 200MHz is targeted as operating frequency and antenna characteristic such as return loss, radiation patter, VSWR etc are targeted to be comparable to Commercial Off-The-Shelf (COTS) product. Antenna design in this paper simulated using Computer Simulation Technique (CST) and introduced Parameter Sweep and Genetic Algorithm (GA) technique to determine the optimal lengths of antenna and stubs. This paper reveal that stubs attached to one sided of monopole antenna is more suitable for single frequency at VHF band and proved that 26.7 % of antenna size reduction can be achieve compare to conventional quarter-wave monopole antenna.